Corrigendum: Editorial: Rising stars in environmental, aviation and space physiology: 2022(Front. Physiol., (2023), 14, (1230752), 10.3389/fphys.2023.1230752) - Saveko, Alina; Washio, Takuro; Petersen, Lonnie G.; Custaud, Marc Antoine; Liphardt, Anna-Maria (Frontiers in Physiology, 2023)
In the published article there was an error in the Author list, whereby author “Anna-Maria Liphardt” was erroneously listed as the second author. The corrected Author list appears below. “Alina Saveko, Takuro Washio, Lonnie G. Petersen, Marc-Antoine Custaud and Anna-Maria Liphardt”. In the published article, there was an error in affiliation for Marc-Antoine Custaud. Instead of “University Angers, CRC, CHU Angers, Inser, CNRS, MITOVASC, SFR CAT, Angers, France”, it should be “CRC, CHU Angers, Inserm, CNRS, MITOVASC, SFR ICAT, University of Angers, Angers, France”. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.
CRIS-Team Scopus Importer:2023-08-11
Keywords: countermeasures; deconditioning; gravitational physiology; integrative physiology; weightlessness